2000
DOI: 10.1039/b000479k
|View full text |Cite
|
Sign up to set email alerts
|

IR spectroscopy as a high-throughput screening-technique for enantioselective hydrogen-transfer catalysts

Abstract: A new high-throughput screening-technique based on IR spectroscopy has been developed for ruthenium catalysed asymmetric transfer-hydrogenation by comparing the reaction rate of the reduction of ketones using (R)-vs. (S)secondary alcohol as the hydrogen donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…To date, a number of techniques are under development for the high-throughput enantiomeric composition determination [13][14][15][16][17], including time resolved IR-thermographic method [18][19][20][21], electron spray mass spectrometry [22][23][24][25][26], capillary electrophoresis [27], UV/Vis [28][29][30], circular dichroism [31,32], and fluorescence [33,34]. Among these approaches, optical methods have been attracting increasing attention due to their ability for quick data collection and compatibility with high-throughput screening system.…”
Section: Advances In Chemistrymentioning
confidence: 99%
“…To date, a number of techniques are under development for the high-throughput enantiomeric composition determination [13][14][15][16][17], including time resolved IR-thermographic method [18][19][20][21], electron spray mass spectrometry [22][23][24][25][26], capillary electrophoresis [27], UV/Vis [28][29][30], circular dichroism [31,32], and fluorescence [33,34]. Among these approaches, optical methods have been attracting increasing attention due to their ability for quick data collection and compatibility with high-throughput screening system.…”
Section: Advances In Chemistrymentioning
confidence: 99%
“…Three years later, van Leeuwen [24] developed a new screening technique to measure the enantiomeric excess of chiral hydrogen-transfer catalysts in the reduction of acetophenone using ephedrine 27 or phenylglycinol 28 as ligands (Scheme 6). A single measurement was sufficient to calculate the enantiomeric excess of each mixture by subtracting a reference spectrum from each sample spectrum.…”
Section: Infrared Spectrometrymentioning
confidence: 99%
“…We conclude that this method nevertheless has some potential in the determination of ee values (and other types of screening). Finally, van Leeuwen has shown that in some cases IR spectroscopy is useful in the evaluation of asymmetric reactions 95…”
Section: High‐throughput Screening Systems For Assaying Enantioselmentioning
confidence: 99%